STEP Skills Measurement Surveys : Innovative Tools for Assessing Skills - Pierre, Gaelle; Sanchez Puerta, Maria Laura; Valerio, Alexandria; Rajadel, Tania (World Bank Group, Washington, DC, 2014)
The Skills Towards Employability and Productivity (STEP) program was designed to better understand the interplay between skills on the one hand and employability and productivity on the other. The STEP program developed survey instruments tailored to collect data on skills in low- and middle-income country contexts. The present note is a reference document for readers seeking background information on the STEP surveys and for users of the data, which is publicly available through the World Bank s Microdata Catalog. The note describes the design of the survey instruments and the constructs measured as well as the technical standards and implementation protocols adopted to ensure data quality and comparability across countries. It also provides guidance to users for the construction of aggregated skills indicators and for the use of the reading literacy assessment data.